First report of Lipoptena axis Maa, 1965, from captive cervids in Thailand, based on morphological and molecular data - Thanwiset, Tiwat; Pitaksakulrat, Opal; Hongsrichan, Nuttanan; Boonmars, Thidarut; Bunchu, Nophawan; Thipphet, Ketsarin; Chaisongkram, Chavin; Ponsrila, Kanda; Kimkamkaew, Siriwan; Rompo, Thanakorn; Kwak, Mackenzie L.; Nakao, Ryo; et al. (Scientific reports, 2024)
Deer louse flies ( Lipoptena spp.) are hematophagous ectoparasites of cervids. The genus Lipoptena comprises 32 species, some of which are of veterinary importance as vectors of various pathogens, and are also known to attack human hosts. Recently, deer louse flies have been observed during annual checkups of captive cervids at Khon Kaen Zoo in Khon Kaen, Thailand. However, data on their specific identity and prevalence remain limited. This study aims to identify louse fly samples from captive cervids at Khon Kaen Zoo using morphological and molecular analyses. A total of 60 louse flies were collected from 17 captive cervids and identified based on their morphology. Major morphological characteristics, including mesothoracic bristle patterns, abdominal tergal plate bristles, and terminalia structure indicated that the Khon Kaen louse fly is Lipoptena axis Maa, 1965. Phylogenetic analysis of sequences from a portion of the mitochondrial cytochrome c oxidase subunit I (COI) gene was performed, which confirmed that L. axis of this study belongs to the cervi group, which is distinct from other groups of Lipoptena species. This study represents the first report of L. axis in Thailand. We provide an updated taxonomic key for the identification of Lipoptena species in the cervi group.